Penggunaan Aplikasi SARETAYES Sebagai Media Pembelajaran Alternatif Untuk Penguatan Literasi Informasi - Muhammad Ainun Najib; Galuh Indah Zatadini (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2023)
This study aims to determine the alternative efforts made by the library to strengthen the literacy of learning information and describe the challenges in the strengthening process. The method used in research is descriptive, where the data obtained using observation techniques, documentation interviews. Data analysis techniques in this study consist of data reduction, data encoding, and conclusion with data validity techniques using triangulation method. The result of this research is the use of Saretayes application as an alternative learning medium to strengthen information literacy in SMPN 1 Rejotangan as an effort made by the library in meeting the learning needs of students. In addition, there are also various challenges in the process of strengthening learning information literacy including internal and external factors. These external factors consist of a pandemic situation that resulted in the library performing semi-open services in meeting information needs, the memory capacity of the device owned by students is inadequate to download applications. While the internal factors consist of the lack of knowledge and understanding in depth related to the application and also the lack of number of companion books provided by the Saretayes application.